Passion toward work and political skills: Validation of scales for the assessment of business managers - Martins, Margarida (2014)
This study presents the validation of the Passion Toward Work Scale (PTWS; Vallerand & Houlfort, 2003) and of the Political Skill Inventory (PSI; Ferris, Treadway, Kolodinsky, Hochwarter, Kacmar, Douglas, & Frink, 2005) for Portuguese business managers. The PTWS consists of 14 items, distributed in two dimensions: obsessive passion and harmonious passion.The PSI consists of 18 items and it includes four dimensions: social astuteness, interpersonal influence, networking ability, and apparent sincerity. There were 131 Portuguese managers participating in the study, from the North, Center and South of Portugal, and from various activity domains, age cohorts, and both genders. Findings suggest that both measures present high levels of precision and that the constructs originally defined by the authors are replicated in the dimensional structure for the Portuguese sample. A statistically significant and positive relation was also found between harmonious passion, assessed with the PTWS,and interpersonal management skills, measured with the PSI.